Exploring Students' Perceptions of Mobile Game-Based Social Studies Learning Model - Wirawan, Gandung; Abdulkarim, Aim; Komalasari, Kokom; Wiyanarti, Erlina (Yupa: Historical Studies Journal, 2022)
This research explores students' perceptions of mobile game-based learning models in social studies instruction. A descriptive quantitative design was used, with a questionnaire survey given to 31 students with experience with mobile game-based learning models. The research results show that students generally have a positive perception of mobile game use in Social Studies learning, with the majority agreeing that mobile games increase their engagement and motivation. The study also identified several factors influencing student engagement and motivation, such as the relevance and quality of game content, the level of interactivity and feedback provided, and integration with the curriculum. The findings show that the mobile game-based learning model can potentially increase students' enthusiasm for learning social studies, especially for Generation Z students accustomed to using digital devices in their everyday lives.